Integrated Uncertainty in Knowledge Modelling and Decision Making 10th International Symposium, IUKM 2023, Kanazawa, Japan, November 2-4, 2023, Proceedings, Part I - Huynh, Van-Nam.; Le, Bac.; Honda, Katsuhiro; Inuiguchi, Masahiro; Kohda, Youji (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
These two volumes constitute the proceedings of the 10th International Symposium on Integrated Uncertainty in Knowledge Modelling and Decision Making, IUKM 2023, held in Kanazawa, Japan, during November 2-4, 2023. The 58 full papers presented were carefully reviewed and selected from 107 submissions. The papers deal with all aspects of research results, ideas, and experiences of application among researchers and practitioners involved with all aspects of uncertainty modelling and management.
Uncertainty Management and Decision Making -- Optimization and Statistical Methods -- Economic Application.
Keywords: Artificial intelligence; Computer science -- Mathematics; Database management; Algorithms; Artificial Intelligence; Mathematics of Computing; Database Management System; Design and Analysis of Algorithms